PELAKSANAAN PROMOSI OBJEK WISATA DANAU MEDUYAN KABUPATEN INDRAGIRI HULU PROVINSI RIAU - Dessy Alencia Lumban Gaol; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research aims to determine about to find out the promotion strategies carried out by the Office of Youth, Sports and Tourism of the Indragiri Hulu Regency. This research to make use qualitative method to analysis set of case, which to become the key informan in this research as much as nine people’s. That is the head of the Tourism Office, the head of tourism, the head of the tourism marketing section, the tourism staff and the head of the pokdarwis of Lake Meduyan. Sources were obtained through observation, interview, and documentation. Based on result of this research, that has been conducted, for the whole of the results of the interview answers said that the promotion of Meduyan Lake tourism objects has been done, but still need to raising required.Keywords : strategy, promotion, tourism.